Analysis of collaborative spectrum sensing without dedicated sensing period. Issue 15 (1st October 2013) - Chen, Yunfei; Tang, Liang; Long, Min
Abstract : Previous works on spectrum sensing use either samples free of secondary user interference based on dedicated sensing period or samples with partly 'cleaned' secondary user interference based on specific characteristics of orthogonal frequency division multiplexing signals or decoded signals. In this article, collaborative spectrum sensing using samples corrupted by secondary user interference without dedicated sensing period or 'cleaning' procedure is studied, and its performance is analysed. Two different cases of primary user signals are considered. In the first case, the primary user signal suffers from fast fading, whereas in the second case, the primary user signal suffers from slow fading. New detectors for these two cases are derived, based on which their performances are analysed. Numerical results show that the diversity gain is lost because of the secondary user interference. For fast‐fading primary user signal, the sensing performance deteriorates quickly when the number of interfering secondary users increases, whereas for slowly fading primary user signal, an error floor exists when the number of interfering secondary users increases. On the other hand, by choosing appropriate system parameters, high sensing accuracy can still be achieved with acceptable loss in detection probability, but with long transmission time when no dedicated sensing period or 'cleaning' procedure are used.